IMPACT OF HYDROXYPROPYL METHYLCELLULOSE (HPMC) TYPE AND CONCENTRATION ON THE SWELLING AND RELEASE PROPERTIES OF PROPRANOLOL HYDROCHLORIDE MATRIX TABLETS USNING A SIMPLEX CENTROID DESIGN - KRAISIT, PAKORN (International Journal of Applied Pharmaceutics, 2019)
Objective: To prepare hydroxypropyl methylcellulose (HPMC) matrix tablets of propranolol hydrochloride (PNL) using a simplex centroid design. Methods: HPMC matrix tablets with different amounts and types of HPMC were prepared by direct compression. A simplex centroid design was used to evaluate tablet weight (Y1), thickness (Y2), hardness (Y3), axial swelling time at 0.5–12 h (Y4-Y9), radial swelling time at 0.5–12 h (Y10-Y15), and % released at 1–12 h (Y16-Y19). Results: The tablet weight, thickness, and hardness were 397.6–400.4 mg, 3.967–4.029 mm, and 106.9–139.0 N, respectively. The % swelling (axial) and % swelling (radial) at 0.5–12 h were-8.715 to 59.889 and-1.887 to 49.287, respectively. The negative % swelling could be attributed to erosion of the tablets. The in vitro release of PNL from the tablets in buffer solution pH 1.2 (1 h) and pH 7.5 (3–12 h) was 21.12–76.22%. Tables with a high proportion of K100M HPMC had high PNL release, and the mechanism of PNL release was diffusion-and erosion-controlled. Conclusion: The simplex centroid design is potentially advantageous for formulating PNL-HPMC matrix tablets.